TEACHING ACADEMIC INTEGRITY IN CHINA: A NEW UNIVERSITY CURRICULUM - Denisova-Schmidt, Elena; Xu, Zhaoheng; Wang, Qi (Journal of Sociology: Bulletin of Yerevan University, 2024)
This paper highlights the global issue of academic integrity, particularly in Chinese higher education institutions (HEIs). While policies and classes on integrity exist, comprehensive training opportunities are lacking. To address this, seminars targeting graduate students at one high-level research university in Shanghai have been initiated, aiming to foster competencies for international collaboration and ethical awareness. In the first seminar, various misconduct cases were discussed, including cheating on coursework, exam impersonation, and academic falsification in the Chinese higher education context. Reflecting on the issues and implications this seminar raised, this paper advocates for continued effort towards developing academic integrity training at Chinese HEIs, which would ultimately contribute to enhancing a culture of integrity in Chinese higher education.